Kontribusi Wanita Nelayan (Istri Nelayan) Terhadap Pendapatan Dalam Upaya Pemenuhan Kebutuhan Ekonomi Keluarga - Mela Rosiana Dewi; Yulhendri Yulhendri (Universitas Negeri Padang, 2021)
This study aims to analyze how much the income of fishermen's households and the contribution made by women fishermen to the household income of fishermen. This research was conducted in Pasie Nan Tigo Subdistrict Koto Tangah Padang City in August 2020. This type of research is descriptive research. Data collection is conducted with interviews, observations and documentation. For the determination of samples used Purposive Sampling technique with the number of samples as many as 37 people. The results of this study showed that 1) income generated by fishing households whose wives dry fish is Rp. 3.078.378,- per month and household income that his wife trades monthly is Rp.3.407.790,-. Factors that affect the income of these fishermen women are educational factors and age factors. 2) The contribution obtained from women fishermen who dry fish is 55% and the contribution of women fishermen who trade 60%.